Single-center Experience with Live Kidney Donors 60 Years of Age or Older. Issue 12 (December 2014) - Gallinat, Anja; Paul, Andreas; Treckmann, Jürgen W.; Molmenti, Ernesto P.; Dittmann, Susanne; Hoyer, Dieter P.; Witzke, Oliver; Minor, Thomas; Sotiropoulos, Georgios C.
Live donor kidney transplantation (LDKT) with elderly donors is a controversial topic. The purpose of this study was to evaluate donor and recipient outcomes involving live donors 60 years of age or older. All LDKTs performed at our institution from January 2000 to January 2011 were evaluated. Statistical analysis included t test, uni- and multivariate regression analyses, and Kaplan-Meier survival analysis. Forty-seven LDKTs were performed with donors 60 years of age or older. Median donor age was 65 years. Fifty-seven per cent were female. Forty-one recipients received their first KT (seven pre-emptive). Initial graft function was documented in 45 patients (96%). After a median follow-up of 69 months, 1-, 3-, and 5-year graft and patient survival rates were 98, 98, and 95 per cent and 96, 94, and 87 per cent, respectively. Univariate Cox proportional hazard analysis showed donor body mass index and previous KT to be predictors of graft survival. Recipient comorbidity index, HLA-B mismatches, and creatinine level at 2 years post-KT were predictors of patient survival. None of these variables remained significant by multivariate analysis. Female gender was the only positive predictor of donor postoperative creatinine levels. Satisfactory long-term donor and recipient outcomes can be achieved with live kidney donors 60 years of age or older. Careful evaluation and selection remain key to success. The role of female gender in donor long-term kidney function should be further investigated.